Use and behavioural intention of m-payment in GCC countries: Extending meta-UTAUT with trust and Islamic religiosity - Wassan Abdullah Alkhowaiter (Journal of Innovation & Knowledge, 2022)
Mobile payments and their applications have grown lucratively across the globe. Yet limited studies have attempted to investigate user's attitude on m-payments and their behavioral intention. Taking this as a research gap, this research investigates the important variables that build a positive attitude, behavioral intention and use towards m-payments by using the meta-UTAUT framework, with Islamic religiosity as a moderating variable. This research follows a single cross-sectional design using a survey methodology. 510 sample was collected from Gulf countries and Structural equation modeling analysis was used to test the proposed conceptual model. The results indicate performance expectancy and facilitating conditions are important variables that structure the dependant variables. Trust is found to be significantly related to behavioral intention and use. Also, Islamic religiosity is found to positively moderating the relationship of behavioral intention to use of m-payments. This research extends the framework of meta-UTAUT with trust and introduces Islamic religiosity as a moderating variable. This research contributes extensively to the m-payment literature and theories associated with meta-UTAUT propositions. With in-depth arguments proposed in hypotheses, the propostions contribute to motivation and social learning theories as well.